What Holds People Together? First‐Person Anthropology and Perspective‐Taking in Thai Ghost Stories. (4th March 2015) - Carlisle, Steven
Abstract: What allows people to share cultural realities? Many theories imply that people orient themselves directly to abstract cultural structures or toward a set of powerful discourses which shape them. But because cultural worlds are understood practically and experienced and communicated through first‐person perspectives, people must engage in empathic perspective taking —orienting themselves toward one another's perspectives—instead. This article explores idiosyncratic Thai interpretations of ghost attacks, shaped by individual and institutionalized experiences. By focusing first on personal perspectives rather than shared conceptions, it proposes that anthropologists can minimize assumptions about shared social and cultural structures in a way that explains how individualized understandings can be accepted by others. Divergent interpretations become comprehensible through empathic reasoning based on shared notions of human nature. This approach contributes to the ongoing anthropological project of minimizing assumptions about what our subjects know and expands anthropology's ability to explore change, intracultural variation, and the relationships between individuals and their cultural contexts.